How to conduct a metaevaluation?: A metaevaluation practice - BERK, ŞABAN (My University, 2023)
A metaevaluation is a quality cross-check to examine the conduct of an evaluation and validate the results. Of the few metaevaluation studies, almost none have reported on the metaevaluation procedure through a practical example evaluation. Tis study reports on the strengths and weaknesses of a program evaluation study in terms of the four main standards: utility, feasibility, propriety, and accuracy. It includes a metaevaluation process that involves both quantitative and qualitative analysis of data from eight meta-evaluators. It was found that while the evaluation study had very good utility and accuracy standards, the feasibility and propriety standards were only fair.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Kütüphanecilik; Social Sciences and Humanities; Sociology; Library Sciences; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; BİLGİ BİLİMİ VE KÜTÜPHANE BİLİMİ; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; INFORMATION SCIENCE & LIBRARY SCIENCE; Kütüphane ve Bilgi Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; Library and Information Sciences; Social Sciences & Humanities; evaluating the evaluation; metaevaluation; metaevaluation practice; program evaluation